1988
DOI: 10.1136/oem.45.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Farming and malignant lymphoma in Hancock County, Ohio.

Abstract: Raised death rates have been reported for non-Hodgkin's lymphoma (NHL) and Hodgkin's disease (HD) among white male residents of Hancock County, Ohio, United States, for 1960-79. As a surveillance activity, to assess the possibility of workplace exposures contributing to these raised rates, a case-control study was conducted using death certificate records of white male Hancock County residents for 1958-83. There were 61 cases of NHL, 15 cases of HD, and 304 control subjects (chosen as a stratified random sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
(3 reference statements)
1
8
0
Order By: Relevance
“…Farmers on intensive chicken farms 54 43 97 33 (9) 32 (9) 32 (9) 8 (6) 6 (6) 7 (6) Workers at chicken slaughterhouses 33 17 50 40 (10) 41 (11) 40 (10) 12 (9) 9 (4) 11 (8) Group exposed to quails: Workers on quail farms including quail slaughter 25 40 65 33 (7) 37* (12) 35 (11) 7 (6) 9 (5) 9 (5) *P < 0 04 men v women. Farmers on dairy or pig farms with poultry (n = 33)% 6-1 33-3 24-2 27-3 6-1 3 0 Group highly exposed to chickens:…”
Section: Serological Testsmentioning
confidence: 99%
“…Farmers on intensive chicken farms 54 43 97 33 (9) 32 (9) 32 (9) 8 (6) 6 (6) 7 (6) Workers at chicken slaughterhouses 33 17 50 40 (10) 41 (11) 40 (10) 12 (9) 9 (4) 11 (8) Group exposed to quails: Workers on quail farms including quail slaughter 25 40 65 33 (7) 37* (12) 35 (11) 7 (6) 9 (5) 9 (5) *P < 0 04 men v women. Farmers on dairy or pig farms with poultry (n = 33)% 6-1 33-3 24-2 27-3 6-1 3 0 Group highly exposed to chickens:…”
Section: Serological Testsmentioning
confidence: 99%
“…1 Other studies have also reported farmers to be at increased risk for NHL, chronic lymphoid leukaemia (CLL), Hodgkin's disease, and multiple myeloma. [2][3][4][5][6][7] Veterinarians are undoubtedly occupationally exposed to zoonotic infectious agents and several studies of cancer in veterinarians have been conducted. Figgs and colleagues 8 reported a significant increased risk of multiple myeloma and Blair et al found elevated proportions of LH cancer deaths among veterinarians.…”
mentioning
confidence: 99%
“…Sixteen of the studies included in the analyses were restricted to white males (10,11,13,15,27,28,30,(34)(35)(36)(37)(38)(39)(40)(41)(42). Five studies reported results only for men (4,12,(43)(44)(45).…”
Section: Resultsmentioning
confidence: 99%
“…Elevated risks have been reported for exposure to fabric dust (3), creosote (4), organic solvents (4,5), chlorophenols (5), and phenoxy acids (4,5). Elevated risks have been reported for wood-related occupations (6), fishermen (7), meat processors (8), and farmers (9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%